The Nexus Between Risk and Investment Factors on Insurance Companies Profit in Indonesia - Purnamawati, I Gusti Ayu (Program Studi Akuntansi FPEB UPI, 2019)
Abstract. This study aims to analyze the nexus between risk factors and investment returns to the profits of insurance companies in Indonesia, using a quantitative approach. The population of this research is insurance companies listed on the Indonesia Stock Exchange. The sampling technique uses purposive sampling. The number of samples is 10 insurance companies. This study uses secondary data with the documentation method, and uses multiple linear regression analysis models. The results showed: risk based capital, underwriting, and investment returns had a significant positive effect on insurance profit, while the claim expense ratio had a significant negative effect on insurance profit. Keywords. Investment; Insurances; Â Profit; Risk.Abstrak. Penelitian ini bertujuan untuk menganalisis hubungan antara faktor-faktor risiko dan pengembalian investasi terhadap keuntungan perusahaan asuransi di Indonesia, menggunakan pendekatan kuantitatif. Populasi penelitian ini adalah perusahaan asuransi yang terdaftar di Bursa Efek Indonesia. Teknik pengambilan sampel menggunakan purposive sampling. Jumlah sampel adalah 10 perusahaan asuransi. Penelitian ini menggunakan data sekunder dengan metode dokumentasi, dan menggunakan model analisis regresi linier berganda. Hasil penelitian menunjukkan: risiko berbasis modal, underwriting, dan pengembalian investasi memiliki pengaruh positif signifikan terhadap laba asuransi, sedangkan rasio biaya klaim memiliki pengaruh negatif signifikan terhadap laba asuransi.Kata kunci. Â Asuransi; Investasi; Laba; Resiko.